2010
DOI: 10.5001/omj.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hypertension among Type II Diabetics

Abstract: Only 30% of the BP of the hypertensive diabetics met the recommended BP for diabetes. More effort should be dedicated to control the BP in diabetics. Physicians should be careful in the selection of hypertensive medications, because in some combinations, they are not useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
8
1
Order By: Relevance
“…Previous studies among Omani patients, at primary health care centers reported similar results. [10][11][12] Our blood pressure control results are similar to tertiary centers in Saudi Arabia, the United Arab Emirates, and Lebanon. [22][23][24] Other studies reported it at 11-36%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies among Omani patients, at primary health care centers reported similar results. [10][11][12] Our blood pressure control results are similar to tertiary centers in Saudi Arabia, the United Arab Emirates, and Lebanon. [22][23][24] Other studies reported it at 11-36%.…”
Section: Discussionsupporting
confidence: 88%
“…[10][11][12] This study assessed the quality of diabetes care at Sultan Qaboos University Hospital (SQUH), a countrywide tertiary referral center in Oman, through the evaluation of HbA 1C , blood pressure, serum lipids and urine albumin/creatinine ratio in a sample of Omani T2D patients. The assessment was done using the American Diabetes Association (ADA) standards of medical care in diabetes and guidelines from the American National Cholesterol Education Program III NCDP NIII Adult Treatment Panel (ATP).…”
mentioning
confidence: 99%
“…Likewise, Al-Nozha et al (2004) found that males were overall having higher prevalence of DM than females in Riyadh capital, Saudi Arabia. Similar findings have been reported in the neighboring countries, such as in Sultanate Oman (El-Shafie & Rizvi, 2010) and in Kuwait (Ahmed, Waslien, Al-Sumaie, Prakash & Allafi, 2013). In addition, the association between diabetes and gender has been the focus of several studies with varying reports.…”
Section: Discussionsupporting
confidence: 67%
“…A study conducted in Spain showed that the presence of diabetes was significantly associated with high blood pressure (OR 2.26 [1.77,2.87]) (Soriguer et al, 2012). Another a study from Sultanate Oman found that 70% of the diabetic patients were found to have high blood pressure (El-Shafie & Rizvi, 2010). Likewise, elsewhere studies have been reported that the risk of diabetes was greater in individuals with hypertension than in those without (Xia et al, 2013;Akter et al, 2014;Zaman & Borang, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation